Pengaruh Dosis Pupuk Phonska Terhadap Pertumbuhan Dan Hasil Beberapa Varietas Kacang Panjang (Vigna sinensis L.) - Afian Bayu Aji Kusuma; Saiful Bahri; Sumarmi Sumarmi (Innofarm:Jurnal Inovasi Pertanian, 2022)
Long beans (Vigna sinensis L.) are shrubs which are a type of leguminous plant. Long beans are creeping upwards. The research was carried out in Hamlet Temulus, Tunggulrejo Village, Jumantono District, Karanganyar Regency, from November 17, 2021 to January 21, 2022. The purpose of this study was to determine the effect of implementing Phonska fertilizer and 3 varieties on the growth and yield of long beans. The experimental design used in this study was a completely randomized block design (CRBD) which was arranged in a Split Plot design consisting of 2 factors. The first factor used 3 varieties, namely Parade tavi, Merah Putih Super and Fagiola IPB. The second factor is the use of 4 doses of Phonska fertilizer, 0 grams, 2.5 grams, 5 grams and 7.5 grams. This research shows that of 2.5 grams of Phonska fertilizer on the varieties of Merah Putih Super and Fagiola IPB on the yield of 4 long bean harvests had an effect on the number of fruits 51.83 and 42.99 fruits.